Hubungan Motivasi Kerja, Karakteristik Individu dan Kompensasi terhadap Disiplin Kerja Perawat Rumah Sakit Cikunir Bekasi Tahun 2018 - Dini Rahmawati Permana (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Discipline is a function of operational human resources management the most important because the better the working discipline employees the better performance is achieved. Factor affecting the discipline of work i.e. the motivation of working nurses to increase productivity, the characteristics of the individuals belonging to each nurse, as well as the existence of the application of the compensation is good for the welfare of nurses. This research aims to look at the description of the work discipline Hospitals Cikunir bekasi as well as find out how relationships work, the characteristics of individual motivation and compensation against the discipline of nursing work in a hospital Cikunir Bekasi. This research uses a quantitative approach with methods "Cross Sectional". The research sample is all over the nurses as much as 30 people were taken with the total sampling method.   Univariate analysis done subsequent to see frequency distribution, bivariat analysis using Pearson Correlation and multivariate analysis using multiple linear regression. The test results showed that the bivariate variables work motivation, compensation and individual characteristics have a significant relationship against the discipline of work. Whereas, in multivariate test of variables of individual characteristics, work motivation and compensation the most dominant effect significantly to the discipline of work i.e. the individual characteristics of the variable with a value of 0.002 0.546 Beta with significance.  To increase work discipline nurses RS Cikunir Bekasi, required the effort of increasing internal and external training of nurses and nursing career, improving the motivation of working nurses by providing a reward or promotion position in accordance with performance assessment the nurse.